The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1098/rspb.2012.0199
|View full text |Cite
|
Sign up to set email alerts
|

O' mother where wert thou? Maternal strategies in the southern elephant seal: a stable isotope investigation

Abstract: Maternal effects are widespread in ecology and can alter the dynamics of a population. We investigated the impact of maternal foraging strategies on offspring weaning mass-a proxy of maternal foraging success and of offspring survival-in southern elephant seals on îles Kerguelen. Using 4 years of data, we modelled pup weaning mass as a two-component mixture and used blood stable isotope values to discriminate between maternal foraging strategies previously identified from bio-logging studies. Carbon isotope ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…A mother's foraging success and her offspring's survival have broader demographic consequences, because survival during the non-breeding phase is the most important determinant of elephant seal abundance [43]. Female elephant seals are also faithful to their individual feeding areas [27], so any variability or persistent change in foraging area quality could be an important determinant of future survival and breeding success [44].…”
Section: Discussionmentioning
confidence: 99%
“…A mother's foraging success and her offspring's survival have broader demographic consequences, because survival during the non-breeding phase is the most important determinant of elephant seal abundance [43]. Female elephant seals are also faithful to their individual feeding areas [27], so any variability or persistent change in foraging area quality could be an important determinant of future survival and breeding success [44].…”
Section: Discussionmentioning
confidence: 99%
“…We found that some females repeatedly weaned heavier pups than others of similar age, perhaps suggesting difference in individual quality (here meaning important but unmeasured traits that contribute to among-individual fitness variation, Wilson and Nussey 2010). Such heterogeneity may arise from genetic makeup (Hunt et al 2004), other phenotypic traits (e.g., physiology), behavior (e.g., diet; Authier et al 2012), and variations in past or present environmental conditions experienced (Lindströ m and Kokko 2002, Chambert et al 2013, Stauffer et al 2013.…”
Section: Individual Heterogeneity and Age-related Variation In Weaninmentioning
confidence: 96%
“…v www.esajournals.org Notwithstanding large within-year variation, the increase in weaning mass that persisted through the 1990s and 2000s is thought to be biologically significant (McMahon et al 2000, Authier et al 2012. A potential pathway for population regulation may thus include improved adult female foraging success, a subsequent increase in weaning mass and associated improvement in juvenile survival.…”
Section: Individual Heterogeneity and Age-related Variation In Weaninmentioning
confidence: 99%
See 1 more Smart Citation
“…Red blood cells (collected before the seal's foraging trip) and plasma samples (collected before and after the seal's foraging trip) were freeze-dried and powdered. Blood plasma can contain high and/or variable lipid content in animals (Cherel et al 2005), so we performed a lipid extraction using cyclohexane following the method used for elephant seals Mirounga leonina (Authier et al 2012). Blood subsamples were weighed (~0.4 mg) with a microbalance, packed in tin containers, and nitrogen and carbon isotope ratios were determined by a continuous flow mass spectrometer (Micromass Isoprime) coupled with an elemental analyser (Euro Vector EA 3024).…”
Section: Stable Isotopesmentioning
confidence: 99%